2006
DOI: 10.2466/pr0.99.7.781-793
|View full text |Cite
|
Sign up to set email alerts
|

Attention Bias Towards Personally Relevant Stimuli: The Individual Emotional Stroop Task

Abstract: The emotional Stroop task is a widely used method for investigating attentional bias towards stimuli due to mood or affect. In general, standardized stimuli are used, which might not be appropriate when investigating individual contextual frameworks. It was investigated whether words chosen to be related to individuals' personal life events would produce more pronounced Stroop interference (as an indicator of attentional bias) than stimuli without any personal relevance. Twenty-six nonclinical subjects, 20 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As reported by Algom et al [2], reading and colour naming are slower with emotional words. In general, patients are even slower to name the colour of a word associated with concerns related to their clinical condition [4, 16]; similarly, Wingenfeld et al [17] reported in normal controls that regardless of the emotional significance of the word, personally relevant stimuli are associated with more pronounced Stroop interference than do stimuli without personal relevance. In this study, we excluded emotional words related to psychotic symptoms in order to avoid this bias.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Algom et al [2], reading and colour naming are slower with emotional words. In general, patients are even slower to name the colour of a word associated with concerns related to their clinical condition [4, 16]; similarly, Wingenfeld et al [17] reported in normal controls that regardless of the emotional significance of the word, personally relevant stimuli are associated with more pronounced Stroop interference than do stimuli without personal relevance. In this study, we excluded emotional words related to psychotic symptoms in order to avoid this bias.…”
Section: Discussionmentioning
confidence: 99%
“…Despite debate (Algom, Chajut, & Lev, 2004), there is increasing evidence that Stroop effects may be domain specific, with greater interference in trait-related but not unrelated areas (Edelstein & Gillath, 2008) and in domains of ideographic importance (Wingenfeld et al, 2006). Reaction times consistent with specificity occurs among smokers (Drobes, Elibero, & Evans, 2006), drinkers (Carrigan, Drobes, & Randall, 2004), persons worried about health (Matthews & MacLeod, 1986), and asthmatics (Jessop, Rutter, Sharma, & Albery, 2004).…”
mentioning
confidence: 99%
“…However, the effect of emotion is magnified by trauma exposure: participants exposed to trauma (e.g., combat, assault) were negatively affected by words relating to their trauma more so than controls (Cisler et al, 2011 ). Even healthy participants who had not been exposed to a traumatic event have demonstrated emotional Stroop interference when the words were related to a personal emotional or stressful event (Wingenfeld et al, 2006 ), suggesting that even non-traumatic events in non-clinical samples can elicit intrusive memories that interfere with attention and inhibitory control.…”
Section: Introductionmentioning
confidence: 99%